Avaliação cinemática da mandíbula e efeito do tratamento por terapia manual e estabilização segmentar da coluna cervical na disfunção temporomandibular - Calixtre, Letícia Bojikian (2018)
The central aims of this PhD thesis were: (1) to verify the reproducibility of kinematic variables during maximum mouth opening (MMO) and (2) to investigate the regional interdependency between the upper cervical spine and the orofacial region, using a randomized controlled trial (RCT) where was collected kinematic and clinical outcomes after a physiotherapeutic treatment for the neck in women with temporomandibular disorders (TMD). Therefore, 4 studies were developed. The First Study investigated the reliability of the kinematic analysis of the jaw movement in asymptomatic subjects. The results showed that the reproducibility of the measures depends on the data analysis and on the variables. Static measurements like jaw radius and width were the most reproducible ones. Furthermore, the interincisal distance during MMO and the angular movements of the jaw in sagittal plane presented the smallest errors and should be used in future studies. In general, the variables with low amplitude were less reproductible, with higher Standard Error of Measurement (SEM) and Minimum Detectable Change (MDC). Finally, the inter-rater comparisons presented larger limits of agreement and more frequent outliers. The Second, Third and Fourth studies were elaborated from one RCT that included 61 women with TMD, divided into two groups: Control Group (CG) and Intervention Group (IG). IG was submitted to 10 sessions of physiotherapy based on manual therapy applied on the upper cervical spine and stabilization exercises to the neck, for 5 weeks. The CG did not get any intervention for 5 weeks. Clinical and kinematic variables were collected on baseline and after 5 weeks by a blind rater. The analysis of the Second study aimed: (1) to determine the effectiveness of the protocol to reduce orofacial pain intensity on IG compared to CG, after and during 5 weeks (2) to verify the differences between the groups after 5 weeks on the following secondary variables: Pressure Pain Threshold (PPT) of the masticatory muscles, mandibular function and headache impact in women with TMD. The results showed significant decrease of orofacial pain intensity since 4 weeks of treatment in comparison to CG and in comparison to baseline. There were no significant differences on PPT and no clinically relevant differences on mandibular function. The Third study was based on a secondary analysis of the RCT in order to (1) provide the Minimum Clinical Important Difference (MCID) from the variables related to orofacial pain, headache impact, sensibility of the masticatory muscles, mandibular function and the performance of deep neck flexor muscles, according to an anchor method of analysis, using the Global Rating of Change Scale (GRCS); (2) verify which outcomes can predict the moderate or large response to the treatment. The analysis provided MCID values for variables related to maximum, minimum and current orofacial pain using Visual Analogue Scale (VAS), for the Mandibular Function Impairment Questionnaire (MFIQ), for the Headache Impact Test (HIT-6), for the PPT of the masticatory muscles, for the MMO measured with a caliper, and for the Craniocervical Flexion Test (CCFT). On the univariate regression analysis, among all the outcomes, the ones related to pain and the HIT-6 presented better capacity of discrimination between patients who largely or moderately got better from those who did not. On the multivariate regression analysis, the combination of minimum pain (or any other pain score) and HIT-6 presented the best capacity of discrimination between patients who largely or moderately improved from those who did not. Finally, the Fourth study focused on two clinical variables and several kinematic variables, with the following objectives: (1) verify the effects of the intervention on the behavior of kinematic variables related to range of motion and coordination of the head and jaw during MMO, speech and chewing in women with TMD; (2) verify the differences between the groups regarding the performance of the deep neck flexor muscles (according to the CCFT) and the perception of the patients regarding their global status of health (according to the GRCS) after the intervention/control. The results showed absence of significant effect of the intervention on the kinematic variable´s behaviour regarding range of motion and coordination between head and jaw during MMO, speech and chewing in women with TMD. On the other hand, the IG presented significant improvement on the GRCS, as well as on the CCFT. In general, this thesis enabled the kinematic evaluation of the jaw in order to investigate the normal or pathologic biomechanical patterns of the jaw, provided reference measures for the interpretation of clinical variables related to TMD, that can be used on the clinical settings and research fields, so future studies can continue to investigate this population. On top of that, this thesis cooperates for the evidence of regional interdependency between the upper cervical spine and the jaw, filling some of the knowledge gaps on the literature and suggesting ideas for future studies.